The balloonist : a novel - Harris, MacDonald, 1921-1993. (Cambridge : Galileo Publishers, 2012)
In 1897, Swedish scientist Gustav Crispin and his two traveling companions travel to the Arctic in a hydrogen powered balloon hoping to be the first to set foot on the North Pole.
Adult
Adult
Keywords: Ballooning -- Fiction; Hot air balloons -- Fiction; Adventure fiction; Ballooning -- Fiction; Balloons -- Fiction; Adventure fiction